The Influence of Green Human Resources Management on Green Employee Engagement Mediated by Green Organizational Culture and Moderated by Green Transformational Leadership (Architecture Image Studies, 2026)
This study aims to analyze the effect of green human resources management on green employee engagement mediated by green organizational culture and moderated by green transformational leadership. The study was conducted using a survey method on 100 employees in all regional offices of Bank Sultra. SEM PLS analysis was used for data analysis and obtained results green human resources management has a negative and significant effect on green employee engagement; green human resources management has a positive and significant effect on green organizational culture; green organizational culture has a positive and significant effect on green employee engagement; green human resources management has a positive and significant effect on green employee engagement mediated by green organizational culture; green human resources management has a positive and significant effect on green employee engagement moderated by green transformational leadership.